Age, Sleep, Fatigue, and Body Mass Index Patterns in Central Java Bus Drivers: Multi-Route Occupational Health Assessment - Nugroho, Bayu Yoni Setyo; Putri, Vira Aditya; Rahmadani, Firsta Vian; Maharani, Luiza Firtiya; Wulandari, Elia Ery; Pratama, Bilal Akbar; Manurung, Putri Diantari (Universitas Airlangga, 2025)
Introduction: Indonesia's growing transportation demands have increased reliance on bus services across Central Java Province. Despite their importance, driver health remains understudied, even as driver factors account for 65% of public transportation accidents. This study investigates differences in health characteristics among bus drivers across three distinct routes: Trans Jateng, BRT Semarang City, and Inter-City Bus Transportation Services Between Semarang-Surakarta. Methods: This quantitative cross-sectional study conducted in Semarang City and Surakarta City examined 210 bus drivers between January 2023-August 2024 using interviews, questionnaires and stature meters. Variables included age, sleep duration, fatigue levels (using the Industrial Fatigue Research Committee questionnaire), and Body Mass Index. Analysis employed Kruskal-Wallis tests followed by Mann-Whitney post-hoc tests with Bonferroni correction. Results: Analysis revealed significant differences across all variables (p<0.001). Trans Jateng drivers (mean age 43.1 years) demonstrated optimal sleep (7.0 hours), low fatigue levels (88.6%), and healthier BMI profiles (74.3% normal). BRT Semarang City drivers (mean age 44.2 years) showed paradoxical characteristics with longest sleep duration (9.5 hours) yet highest fatigue levels (80% very high) and poor BMI profiles (84.3% overweight/obese). Inter-City drivers, despite being older (mean age 51.4 years) with shortest sleep duration (5.4 hours), showed moderate fatigue adaptation (92.9%) and similar BMI concerns (84.2% overweight/obese). Conclusion: Significant differences (p<0.001) exist among three public transport driver groups. Trans Jateng showed the best health profile, BRT Semarang City paradoxical with long sleep yet high fatigue, and Inter-City adaptive despite insufficient sleep. Sleep duration does not correlate with fatigue levels. Group-specific health interventions are needed.